Paul Gayler's sauce book 300 world sauces made simple - Gayler, Paul; Jung, Richard (London Kyle Books, 2015)
Starting with French classics such as mayonnaise, hollandaise and veloute sauces, the author covers all the basics and then suggests variations such as adding orange to a hollandaise or olives to a bearnaise.
Keywords: Sauces